Building quality teamwork to achieve excellence in business organizations - Tripathy, Mitashree (International Research Journal of Management, IT & Social Sciences, 2018)
Business organizations are continuously and rapidly expanding. Gone are the days when only individualâs talent and abilities that were counted upon. Business organizations today have found out that the key factor of achieving more and better results at work is when individuals of diverse abilities are formed into a team. This ability to work as part of a team is one of the most imperative skills today. Business organizations are looking for individuals who can not only furnish their own ideas but also who would like to create and develop projects and plans with equally talented people. This paper emphasizes the need and importance of working in a team based organizational setting and also focuses on the five stages of development o a team in the organization.